Comparison between headfirst and tail-first direction of sperm for intracytoplasmic sperm injection - Pongsuthirak, Pallop (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intracytoplasmic sperm injection (ICSI) is used for assisted fertilization. Sperm can be injected headfirst and tail-first. This study aimed to investigate the effect of the headfirst or tail-first injection of sperm into the cytoplasm during ICSI on oocyte survival, fertilization, blastocyst development, implantation, and clinical pregnancy. Methods: A prospective study was carried out by enrolling 79 women who had undergone IVF with male factor infertility between September 2016 and June 2019. The sibling oocytes were randomly inseminated by headfirst ICSI (405 oocytes) and tail-first ICSI (393 oocytes). After fertilization, the embryos were cultured until blastocyst and single embryos were transferred under ultrasound guidance. Results: There was no difference in survival rates (98.8% versus 98.9%; p=0.551), fertilization rate (71.5% versus 74.8%; p=0.333), and formation of blastocysts (50.7% versus 51.2%; p=0.970) between headfirst and tail-first direction of sperm during ICSI. Implantation and clinical pregnancy were also not significantly different. Conclusions: The outcomes showed that the direction of sperm injection (headfirst and tail-first) had no significant effect on oocyte survival, fertilization, blastocyst development, implantation, and clinical pregnancy.